The Effect of Job Satisfaction, Organizational Commitment on Turnover Intention and Employee Performance At PT JJ Gloves Indo Company - Adiyono M; M. Farid Wajdi; Jati Waskito; Anton Agus Setyawan (International Journal of Management Science and Information Technology, 2023)
This study aims to determine the impact of job satisfaction and organizational commitment on turnover intention and its effect on employee performance in the context of PT. JJ Gloves Indo is a manufacturing company. No previous research has studied this relationship at PT JJ Gloves Indo. This research was conducted using quantitative methods. A questionnaire survey was conducted on 200 staff members working in the production department. Data was collected through a proportional sampling technique. Structural Equation Model (SEM) from the Partial Least Square (PLS) program package was used to analyze the data to determine whether there is a relationship between the research variables. The results of this study show that job satisfaction and organizational commitment have a significant direct effect on turnover intention and employee performance. However, turnover intention does not have a significant direct effect on employee performance and cannot mediate the effect of job satisfaction and organizational commitment on employee performance, this states that any change in turnover intention either in the condition of direct influence or as a mediator will not reduce or increase employee performance. This suggests that maintaining job satisfaction and organizational commitment can help reduce turnover intention and improve employee performance.